Urethrocystoscopy of the urinary system in dogs and cats. Issue 9 (1st October 2015) - Lhermette, Philip
Abstract : Conditions of the lower urinary tract are common in dogs and cats and are frequently investigated using various imaging techniques such as ultrasonography and radiography. While not obviating the need for these techniques, urethrocystoscopy provides the clinician with a unique view of the lower urinary tract due to well‐illuminated, magnified, high‐quality images that can show small lesions that are not visible by other means. The images are also more easily interpreted than grainy ultrasound images and radiographs. This article discusses the equipment required and the technique for performing successful urethrocystoscopies in dogs and cats, together with some of the common conditions found and endoscopic treatments available.